2017
DOI: 10.1542/peds.2016-1507
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Price Information on the Ordering of Images and Procedures

Abstract: The effect of price information on ordering rates appears to depend on whether the clinician is pediatric-focused or adult-oriented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Another 6 studies were added from those identified by pearling reference lists for a total of 13 studies [10][11][12][13][14][15][16][17][18][19][20][21]26 for the final analysis. The results constituted 8 randomized controlled trials, 10,12,15,16,18,20,21,26 2 interrupted time series studies, 14,19 2 controlled clinical trials 11,13 and a prospective comparative study. 17 The sequence describing the above process can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Another 6 studies were added from those identified by pearling reference lists for a total of 13 studies [10][11][12][13][14][15][16][17][18][19][20][21]26 for the final analysis. The results constituted 8 randomized controlled trials, 10,12,15,16,18,20,21,26 2 interrupted time series studies, 14,19 2 controlled clinical trials 11,13 and a prospective comparative study. 17 The sequence describing the above process can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Designs of the studies varied as described above. Randomized studies differed based on level of randomization (Four at the level of test, 15,16,21,26 2 at the level of ordering provider, 18,20 1 at the level of patient 12 and 1 at the level of physician's computer session 10 ) The population and the setting in which the studies were done also varied (Four studies done in a community outpatient setting where providers who completed graduate medical education practiced, 11,14,18,20 9 studies done in hospital and outpatient settings of teaching hospitals 10,12,13,[15][16][17]19,21,26 ) The design of the price display also varied (2 studies displayed cost data, 18,20 2 studies utilized hospital input cost, 17,19 7 studied used charge data 10,12,[14][15][16]21,26 and 2 studies displayed wholesale market price 11,13 )…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations